2018
DOI: 10.1371/journal.pone.0198212
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with an outbreak of hospital-onset, healthcare facility-associated Clostridium difficile infection (HO-HCFA CDI) in a Mexican tertiary care hospital: A case-control study

Abstract: ObjectiveTo identify clinical and environmental factors associated with an outbreak of hospital-onset, healthcare facility-associated Clostridium difficile infection (HO-HCFA CDI).DesignCase-control study.SettingPublic, acute care, academic tertiary referral center in Mexico.PatientsAdults hospitalized ≥48 hours between January 2015 and December 2016 were included. Cases were patients with a first episode of HO-HCFA CDI. Controls were patients with any other diagnosis; they were randomly selected from the hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“… 31 Additionally, in a case-control study conducted at a tertiary hospital in Mexico, previous antibiotic use was more frequent (95.9% vs 79.9%; p < 0.001) and the number of antibiotics used was higher (3 vs 2; p < 0.001) in cases versus controls, respectively. 32 Similarly, another case-control study conducted at a tertiary care hospital in Mexico found that prior antibiotic exposure was the most significant risk factor associated with CDI. 33 A systematic review of studies in Brazil from 1988 to 2018 also concluded that the major risk factors for CDI were the number of previous antibiotics and duration of therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 31 Additionally, in a case-control study conducted at a tertiary hospital in Mexico, previous antibiotic use was more frequent (95.9% vs 79.9%; p < 0.001) and the number of antibiotics used was higher (3 vs 2; p < 0.001) in cases versus controls, respectively. 32 Similarly, another case-control study conducted at a tertiary care hospital in Mexico found that prior antibiotic exposure was the most significant risk factor associated with CDI. 33 A systematic review of studies in Brazil from 1988 to 2018 also concluded that the major risk factors for CDI were the number of previous antibiotics and duration of therapy.…”
Section: Discussionmentioning
confidence: 95%
“… 28 Similarly, hospital-based studies from Brazil and Mexico found a significant association with development of CDI and carbapenem use. 32 , 36 Conversely, a study of eight university hospitals in Brazil found exposure to fluoroquinolones to be the only variable associated with development of CDI, whereas carbapenem exposure was not significantly associated. 37 …”
Section: Discussionmentioning
confidence: 99%
“…The most frequent comorbidities in Mexican COVID-19 patients are hypertension, obesity and diabetes, unlike patients admitted to this hospital before conversion. 8 Following conversion, no external patients with preexisting CDI were hospitalized, reducing environmental contamination. These features seemed to overcome the deleterious effect of the high rate of antibiotic use in patients after conversion.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term antibacterial therapy causes a risk of tendinopathy in patients [24][25][26]. Another risk also includes Clostridiodes difficile infection, which is more commonly observed when concurrent proton-pump inhibitor therapy is given to the patient [27,28]. Our patient had been taking Ciprofloxacin.…”
Section: Discussionmentioning
confidence: 95%